Cardiac Autonomic Function in Adults Born Preterm - Karvonen, Risto; Sipola, Marika; Kiviniemi, Antti; Tikanmäki, Marjaana; Järvelin, Marjo-Riitta; Eriksson, Johan G.; Tulppo, Mikko; Vääräsmäki, Marja; Kajantie, Eero (The Journal of Pediatrics, 2020)
Objective To evaluate cardiac autonomic function in adults born preterm. Study design We studied the association between prematurity and cardiac autonomic function using heart rate variability measurements in 600 adults (mean age of 23.3 years) from a geographically based cohort in Northern Finland. There were 117 young adults born early preterm (= 37 weeks, controls). Autonomic function was analyzed by calculating time and frequency domain heart rate variability measurements using linear regression. Results Compared with controls, the mean difference in root mean square of successive differences (indicating cardiac vagal activity) was -12.0% (95% CI -22.2%, -0.5%, adjusted for sex, age, source cohort, and season P = .04) for the early preterm group and -7.8% (-16.8%, 2.0%, P = .12) for the late preterm group. Mean differences with controls in low frequency power (indicating cardiac vagal activity, including some sympathetic- and baroreflex-mediated effects) were -13.6% (-26.7%, 1.8%, P = .08) for the early pretermgroup and -16.4% (-27.0%, -4.3%, P = .01) for the late preterm group. Mean differences in high frequency power (quantifying cardiac vagal modulation in respiratory frequency) were -19.2% (-36.6%, 2.9%, P = .09) for the early preterm group and -13.8% (-29.4%, 5.3%, P = .15) for the late preterm group. Differences were attenuated when controlled for body mass index and physical activity. Conclusions Our results suggest altered autonomic regulatory control in adults born preterm, including those born late preterm. Altered autonomic regulatory control may contribute to increased cardiovascular risk in adults born preterm. Peer reviewed